Single-cell transcriptome revealed dysregulated RNA-binding protein expression patterns and functions in human ankylosing spondylitis - Ren, Zheng; Li, Chenyang; Wang, Jing; Sui, Jiangtao; Ma, Yuan (Frontiers in Medicine, 2024)
Objective: To explore the expression characteristics and regulatory patterns of RBPs in different immune cell types of AS,and to clarify the potential key role of RBPs in the occurrence and development of AS disease.Methods: PBMC sample data from scRNA-seq (HC *29, AS*10) and bulk RNA-seq (NC*3, AS*5) were selected for correlation analysis.(1) Compared with the HC group, the numbers of B, DC (dendritic cells), CD14 + Mono and CD8 + T cells were increased in AS group,while the numbers of platelet (platelets),CD8 + NKT, CD16 + Mono (non-classical monocytes),Native CD4 + T and NK were decreased.(2) Through the analysis of RBP genes in B cells, some RBPs were found to play an important role in B cell differentiation and function, such as DDX3X, SFPQ, SRRM1, UPF2; It may be related to B-cell receptor, IgA immunity, NOD-like receptor and other signaling pathways.(3) Through the analysis of RBP genes in CD8 + T cells, some RBPs that play an important role in the immune regulation of CD8 + T were found, such as EIF2S3, EIF4B, HSPA5, MSL3, PABPC1 and SRSF7; It may be related to T cell receptor, TNF, IL17 and other signaling pathways.(4) Based on bulk RNA-seq, it was found that compared with HC and AS patients, differentially expressed variable splicing genes (RASGs) may play an important role in the occurrence and development of AS by participating in transcriptional regulation,protein phosphorylation and ubiquitination, DNA replication, angiogenesis, intracellular signal transduction and other related pathways.RBPs has specific expression characteristics in different immune cell types of AS patients, and has important regulatory functions. Its abnormal expression and regulation may be closely related to the occurrence and development of AS.